Psychometric properties of the French borderline symptom list, short form (BSL-23). Issue 1 (December 2016) - Nicastro, Rosetta; Prada, Paco; Kung, Anne-Lise; Salamin, Virginie; Dayer, Alexandre; Aubry, Jean-Michel; Guenot, Florence; Perroud, Nader
Abstract Background The short form of the Borderline Symptom List (BSL-23) is a self-rating instrument used to assess specific symptoms of borderline personality disorder (BPD). The original German version has shown good psychometric proprieties. The BSL-23 can also be used to measure the effects of therapy on patients with BPD. The aim of this study was to assess the psychometric properties of the French version of the BSL-23. Methods The French version of the BSL-23 was given to 265 subjects with BPD. Factor structure, reliability, test-retest stability, convergent validity, divergent validity, and sensitivity to change were analysed. Forty-five subjects suffering from attention-deficit hyperactivity disorder (ADHD) were used as controls to evaluate the specificity of BSL-23. Results A one-factor structure was obtained in the French version of the BSL-23, showing high internal consistency (Cronbach's alpha = .94) and test-retest reliability (r = .841). The French version of the BSL-23 was highly correlated with depression severity, hopelessness, anger, motor impulsiveness, and BPD diagnosis. It was an efficient tool to discriminate between BPD patients and ADHD patients, and showed good sensitivity to change in a group of BPD patients who took part in a one-month DBT intervention. Conclusions The French version of the BSL-23 shows similar psychometric properties as the original German version. This study therefore provides clinicians and researchers with a French instrument to measure BPD symptomatology.